2017
DOI: 10.1080/10408398.2017.1329198
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anticancer properties of berries

Abstract: The enduring relationship between dietary patterns and human health has led us to investigate the bioactive components present in fruits and vegetables for a very long time. Berries, notably the popular ones such as strawberry, raspberry, blueberry, blackberry, and the Indian gooseberry, are among the best known dietary sources due to the presence of a wide range of bioactive nutritive components. Bioactive components in berries include phenolic compounds, flavonoids, and tannins apart from vitamins, minerals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 159 publications
0
92
0
1
Order By: Relevance
“…C3G is a potent antioxidant that displays anticancer properties in vitro and in vivo (Baby, Antony, & Vijayan, ; Liang et al., ; Zhou, Wang, Zhang, & Zhao, ), the health benefits, such as antioxidant properties, cardioprotective capacity, http://anti-inflammatory attract researchers’ eyes in many reports (Jiang et al., ; Li et al., ; Meng et al., ). The results of this study revealed that C3G and C3G liposomes can enhance the activity of GSH, SOD, and T‐AOC and decrease the MDA content after the H 2 O 2 treatment in Caco‐2 cells in certain concentrations in 2D and 3D cell culture models.…”
Section: Discussionmentioning
confidence: 99%
“…C3G is a potent antioxidant that displays anticancer properties in vitro and in vivo (Baby, Antony, & Vijayan, ; Liang et al., ; Zhou, Wang, Zhang, & Zhao, ), the health benefits, such as antioxidant properties, cardioprotective capacity, http://anti-inflammatory attract researchers’ eyes in many reports (Jiang et al., ; Li et al., ; Meng et al., ). The results of this study revealed that C3G and C3G liposomes can enhance the activity of GSH, SOD, and T‐AOC and decrease the MDA content after the H 2 O 2 treatment in Caco‐2 cells in certain concentrations in 2D and 3D cell culture models.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the composition and the content of these compounds are dependent on the plant species, production status, agricultural processing, and storage, berries are an excellent source of polyphenols, flavonoids, and anthocyanins [20,21], which have been related to their potential beneficial effects on health.…”
Section: Berriesmentioning
confidence: 99%
“…Polyphenols or phenolic compounds are phytochemicals that result from the secondary metabolism of plants coming from the metabolic pathway of shikimic acid and acetate-malonate. They are composed of various chemical structures characterized by an aromatic nucleus of benzene substituted by a hydroxyl group called phenol [21]. Differences between subclasses are given by the number of phenolic rings and the elements attached to them, thus creating several families of compounds, such as flavonoids, anthocyanins, flavones, tannins, and coumarins, among others [21,[27][28][29].…”
Section: Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…They exert multiple biological effects, including antioxidant activity [1] [2], anti-inflammatory [3] [4], anti-cancer [5] [6] and neuroprotective properties [7]. Lipid oxidation has been recognized as the major source of deteriorative changes in the nutritional properties of fats and oils, and the anti-oxidative effects of flavonoids improve the stability of lipid containing foods.…”
Section: Introductionmentioning
confidence: 99%